The Data Envelopment Analysis to Determine Efficiency of Latin American Countries for Greenhouse Gases Control in Electric Power Generation - Sanchez, Leadina; Vásquez, Carmen; Viloria, Amelec (International Journal of Energy Economics and Policy, 2018)
The objective of this research is to determine the efficiency of Latin American countries for the control of GHG emissions due to the generation of electrical energy using the Data Envelopment Analysis (DEA). A positivist epistemic position is assumed, and a methodology of evaluative character is used, comprising five (5) phases. The results show that the countries that are located on the efficient frontier have common police like the increase in the share of renewable energies, and diversification of the energy matrix, which means a better control of GHG emissions. It is possible to determine the efficiency of the public policies established by the countries of Latin America for the control of GHG emissions. In conclusion, the countries that are located on the efficient frontier are those that generate electricity with predominantly renewable sources or, at least, use natural gas as a fuel in greater proportion. Keywords: Greenhouse Gases (GHG), efficient frontier, Data Envelopment Analysis. JEL Classifications: C1, Q4, Q5